Алгоритм автоматизованої обробки сигналу ранніх аудиторних викликаних потенціалів - Григорович, С. В. (ХНУРЕ, 2023)
Auditory brainstem response (ABR), also called short-latency auditory evoked potential, is a type of electrophysiological response happening on the brainstem level within 10 ms of an auditory stimulation. It’s mainly used to assess hearing function in populations, which can’t provide reliable audiogram feedback, as well as an objective measure of a hearing function. Like most brain-derived signals, ABR signal is subject to considerable artifact and needs to be processed before diagnostically useful data can be extracted. This paper is dedicated to a short, fairly simple algorithm that can be used to automatically process raw ABR signals.